Swarm robots search based on artificial physics optimisation algorithm. (1st January 2013) - Xie, Liping; Yang, Gangjun; Zeng, Jianchao; Cui, Zhihua
Swarm robotic is an important research area of swarm intelligence. Swarm robots searching potential target provides a better way in victim search or rescue operations in some disaster scenarios. This paper uses artificial physics optimisation (APO) algorithm as the modelling tool for solving swarm robots searching problem. Firstly, viewed as an individual moving in a closed two-dimensional workspace, each robot is abstracted as one order inertial element. Further, the model of swarm robots search for target with global sense based on APO algorithm is given, in which the virtual force law among robots is constructed through referring the attraction-repulsion rule of APO. Simulation results under an ideal environment show that APO is a feasible and effective when applied to swarm robotic search for target with global sense.